2019
DOI: 10.1186/s13046-019-1359-9
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor β inhibits breast cancer cells migration and invasion through CLDN6-mediated autophagy

Abstract: Background Estrogen receptor β (ERβ) has been reported to play an anti-cancer role in breast cancer, but the regulatory mechanism by which ERβ exerts this effect is not clear. Claudin-6 (CLDN6), a tight junction protein, acts as a tumor suppressor gene in breast cancer. Our previous studies have found that 17β-estradiol (E2) induces CLDN6 expression and inhibits MCF-7 cell migration and invasion, but the underlying molecular mechanisms are still unclear. In this study, we aimed to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 60 publications
4
89
0
Order By: Relevance
“…Still, comparison of both cell lines relative levels of ERα/β expression shows that nuclear estrogen receptors are rather insignificantly involved in the MDA-MB-231 cellular response to red clover isoflavones, but they may be involved in other non-genomic intracellular action. These results are consistent with data presented in other studies, where a low-invasive MCF-7 cell line reported as an ER-positive cellular model expressed both types of estrogen receptors, whereas highly-invasive MDA-MB-231, known as ER-negative one, expressed ERβ [50,51]. As it is shown in Figure 8; Figure 9C,D, red clover extracts revealed no significant influence on ERβ and ERα mRNA expression and protein levels.…”
Section: The Influene Of Trifolium Pratense L On Gene Expressionsupporting
confidence: 92%
See 1 more Smart Citation
“…Still, comparison of both cell lines relative levels of ERα/β expression shows that nuclear estrogen receptors are rather insignificantly involved in the MDA-MB-231 cellular response to red clover isoflavones, but they may be involved in other non-genomic intracellular action. These results are consistent with data presented in other studies, where a low-invasive MCF-7 cell line reported as an ER-positive cellular model expressed both types of estrogen receptors, whereas highly-invasive MDA-MB-231, known as ER-negative one, expressed ERβ [50,51]. As it is shown in Figure 8; Figure 9C,D, red clover extracts revealed no significant influence on ERβ and ERα mRNA expression and protein levels.…”
Section: The Influene Of Trifolium Pratense L On Gene Expressionsupporting
confidence: 92%
“…Since estrogenicity is connected with cell proliferation, we evaluated indirectly estrogenic-like effects of T. pratense phenolics at dosages lower than IC0 through the measurement of MCF-7 cells with crystal violet staining. Figure 9C presents the ratios of the proliferative effects of extracts and 17 β-estradiol described by the RPE parameter, where total agonist induces RPE between 80% and 100%, partial agonists induce 25% to 80% and a weak agonist induces between 10% and 25% These results are consistent with data presented in other studies, where a low-invasive MCF-7 cell line reported as an ER-positive cellular model expressed both types of estrogen receptors, whereas highly-invasive MDA-MB-231, known as ER-negative one, expressed ERβ [50,51]. As it is shown in Figure 8; Figure 9C,D, red clover extracts revealed no significant influence on ERβ and ERα mRNA expression and protein levels.…”
Section: The Influene Of Trifolium Pratense L On Gene Expressionsupporting
confidence: 92%
“…Lu et al demonstrated that SMAD2 causes downregulation of claudin-6 by DNA (cytosine-5)-methyltransferase 1 (DNMT1)-mediated DNA methylation, which results in increased migration and invasion of breast cancer cells [105]. In addition, research has shown that estrogen receptor β (ERβ) plays an anti-cancer role in breast cancer, and Song et al demonstrated that this effect is mediated by claudin-6 [106]. On the other hand, Yang et al demonstrated that claudin-6 affects chemo-resistance in MDA-MB-231 cells in response to adriamycin (ADM) by reducing the drug-induced apoptosis [107].…”
Section: Claudins In Breast Cancermentioning
confidence: 99%
“…Many natural compounds and synthetic agents exhibit their anticancer effects through triggering autophagic cell death (Law et al, 2017;Xu et al, 2019;Kiruthiga et al, 2020;Pellerito et al, 2020). Moreover, the activation of autophagy-related signaling may implicate the suppression of certain other cancer therapeutic target to help against cancer, such as tumor invasion and migration and tumor angiogenesis Jiang et al, 2019;Song et al, 2019).…”
Section: Introductionmentioning
confidence: 99%